The Grouping Practices of Teachers in Small Two-Teacher Primary Schools in the Republic of Ireland - Catherine Mulryan-Kyne (Journal of Research in Rural Education, 2005)
Research shows that educational outcomes are no different for pupils in single-grade and multigrade classes. However, little is known about the instructional practices of multigrade teachers. What is known suggests that multigrade teachers tend to employ instructional practices that are not likely to facilitate effective teaching and learning. The present study explored the grouping practices of primary teachers in the Republic of Ireland in small two-teacher multigrade schools. These teachers taught four grade levels together. Results showed that teachers used a wider range of grouping approaches across and within subject areas than has been suggested in previous research. Also, unlike teachers in previous studies, teachers in the present study used cross-age and peer tutoring and across-grade grouping. Results supported previous research regarding the amount of independent seatwork engaged in by pupils in multigrade classrooms. However, pupils in study classrooms also engaged in paired/group seatwork. Further research on teaching practices in multigrade classes, across a range of contexts, is recommended in order to provide a basis for the preparation and support of multigrade teachers.